2019
DOI: 10.1002/csr.1878
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internal control, external assurance, and integrated reports on market value

Abstract: It is generally assumed that the credibility of a firm's disclosure is enhanced when there is an independent review. This is the basis for the requirement that an independent audit firm attest to the veracity of financial statements. With the passage of Sarbanes-Oxley, publicly-traded North American firms must include a statement about the quality of their internal control system in their financial statements. While the audit of the statements of financial position may be considered to pertain only to that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 101 publications
(132 reference statements)
2
34
1
1
Order By: Relevance
“…Given the preliminary nature of the studies and their findings, the construct validity of the IR proxy used (IR self‐constructed indexes are based on subjective judgments) and the research design choices of these studies (i.e., to include all necessary control variables in the model, to run robustness checks, to control for endogeneity) are open to critique, and there are several opportunities for further research, for example, there are few studies comparing the value relevance of IR information with the value relevance of stand‐alone EG report (Mervelskemper & Streit, 2017; van der Meijden, 2016) and there is a paucity of empirical studies focused on the quality of IR information disclosure, and on the role played by an external form of assurance of nonfinancial information disclosed through IR on the association between IR information disclosure and the market value of the firm (Caglio, Melloni, & Perego, 2020; Gal & Akisik, 2020; Landau et al, 2020). Furthermore, there are few studies investigating the role of other external factors, such as cultural context, or internal factors, such as the board of directors or ownership structures, in affecting the IR/market outcomes association (Raimo, Vitolla, Marrone, & Rubino, 2020; Vena et al, 2020; Vitolla, Raimo, & Rubino, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given the preliminary nature of the studies and their findings, the construct validity of the IR proxy used (IR self‐constructed indexes are based on subjective judgments) and the research design choices of these studies (i.e., to include all necessary control variables in the model, to run robustness checks, to control for endogeneity) are open to critique, and there are several opportunities for further research, for example, there are few studies comparing the value relevance of IR information with the value relevance of stand‐alone EG report (Mervelskemper & Streit, 2017; van der Meijden, 2016) and there is a paucity of empirical studies focused on the quality of IR information disclosure, and on the role played by an external form of assurance of nonfinancial information disclosed through IR on the association between IR information disclosure and the market value of the firm (Caglio, Melloni, & Perego, 2020; Gal & Akisik, 2020; Landau et al, 2020). Furthermore, there are few studies investigating the role of other external factors, such as cultural context, or internal factors, such as the board of directors or ownership structures, in affecting the IR/market outcomes association (Raimo, Vitolla, Marrone, & Rubino, 2020; Vena et al, 2020; Vitolla, Raimo, & Rubino, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Wahl et al (2020),Gal and Akisik (2020),Loprevite et al (2019a, b) andCamodeca et al (2018) did not state any significant relationship between IR adoption and the market value of equity (Tobin's Q), whereasLandau et al (2020) reported a negative link.…”
mentioning
confidence: 82%
“…However, Landau et al (2020) have stated that IR assurance by a Big Four audit firm and recognition of the Global Reporting Initiative (GRI) standards do not moderate the relationship between IR adoption and the market value of equity in voluntary IR settings. Gal and Akisik (2020) and Akisik and Gal (2019) found that IR assurance by an accounting firm moderates the link between IR adoption and financial performance as well as between IR adoption and the market value of equity. Maroun (2019) noted that IR assurance by a Big Four audit firm strengthens the positive impact of IR assurance on IR quality in South Africa.…”
Section: Ir Moderator Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…By connecting all material financial and nonfinancial information that determine a firm's ability to create value over the short, medium, and long term into one cohesive business report, IR intends to increase the decision usefulness and transparency of the information disclosed to investors (Garcia‐Sanchez, Martinez‐Ferrero, & Garcia‐Benau, 2019; IIRC, 2013; Vitolla, Raimo, & Rubino, 2019). In accordance with IR's primary focus on providers of financial capital and its aim to increase capital allocation efficiency (IIRC, 2013), the preparation of an integrated report has been shown to decrease information asymmetries (Frias‐Aceituno, Rodriguez‐Ariza, & Garcia‐Sanchez, 2014; Garcia‐Sanchez & Noguera‐Gamez, 2017; Lee & Yeo, 2016) and to result in positive capital market reactions, such as increased firm value (Barth, Cahan, Chen, & Venter, 2017; Gal & Akisik, 2020; Lee & Yeo, 2016), higher stock liquidity (Barth et al, 2017), less transient investors (Serafeim, 2015), higher analyst forecast accuracy, lower cost of equity (Zhou, Simnett, & Green, 2017), and a lower weighted average cost of capital (Vena, Sciascia, & Cortesi, 2020).…”
Section: Introductionmentioning
confidence: 99%